Highly Efficient Inverted Phosphorescence OLEDs Based on Ultrathin Emitting Layer. Issue 1 (June 2014) - Liu, Jun; Wu, Xinkai; Shi, Xingdong; Wang, Jing; Huang, Saijun; Chen, Chaoping; Lu, Jiangang; Su, Yikai; He, Gufeng
Abstract In this paper, we present highly efficient inverted phosphorescence organic light‐emitting diodes (PhOLEDs) based on ultrathin emitting layers (EML). By introducing 1.5 nm EML with co‐host, the inverted PhOLED exhibits external quantum efficiency (EQE) of 31.1%. Besides, a multilayer mCP/MoO3/Al/Cs2CO3 works well as charge generation unit (CGU) for tandem inverted PhOLED with 0.5 nm EML.